(untitled) (Revista de Ciências Agroveterinárias, 2012)
Beans seeds of Germoplasm bank from Santa Catarina State University (BAF/UDESC), Lages, SC, harvested in 2008/2009 e 2009/2010 seasons, were used in sanity tests of seeds with the objective to evaluate the incidence of fungus Colletotrichum lindemuthianum. The media culture were tested of Potato-Dextrose-Ágar (PDA) and V-8 (tomato juice) and the Blotter Test Method. Evaluated 17 and 13 accesses in 2009 and 2010, respectively, including in two years four commercial cultivates: Pérola, BRSSupremo, SCS 202 Guará and IPR- Uirapuru. For each analyzed material were cultivated 200 seeds, ordered in four repetitions of 50 seeds. The seeds were incubated during ten days in growing chamber with photoperiod of 12 hours and temperature of 21°C. The C. lindemuthianum fungus was not detected in accesses BAF51 e BAF86 analyzed in 2009. The media V8 presented itself like the best method of detection and the cultivate SCS 202 Guará presented most of incidence of pathogen among the tested accesses. In 2010 the fungus was detected in all access, and there wasn’t significant difference between substrates, however there was significant difference between the tested accesses, most wile BAF07 presented most incidence of pathogen. The presence of the fungus C. lindemuthianum in the accesses seeds of the Germoplasm Bank of Bean UDESC indicates the need to adopt control measures to reduce their incidence on seeds.